The comparative effect of static vs. dynamic stretching on hamstring flexibility and performance in teenage taekwondo students - Hyun, Woojin; Valleser, Christian Wisdom M. MSHMS (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2025)
Taekwondo characterizes dynamic and high-level kicking technique, thus, a high level of hamstring flexibility is necessary for enhancement of the performance. This study was designed by quasi-experiments. The 10 participants, aged between 13 and 19 years old, were selected by convenience sampling; 5 participants in each stretching intervention. The gathered data was analyzed by paired T-tests to compare the pre-tests and post-tests differences of the flexibility level on hamstring and performance within each group. If significant differences were observed, the effect size would be evaluated using Cohen's d to evaluate the magnitude of the effect. All tests were done at α=0.05 level of significance. Results showed that both static and dynamic stretching methods significantly improved the measured height kicking and sit-and-reach tests among the participants. However, significant improvements in the right and left front leg split tests were observed only in the static stretching group. When comparing static and dynamic stretching, no significant differences were found overall, suggesting that both methods are effective in enhancing flexibility and performance. In general, static stretching tends to be more effective for individuals requiring greater range of motion and flexibility particularly when used in a warm-up routine. On the other hand, dynamic stretching is especially beneficial for athletes engaged in explosive or high-intensity activities where joint mobility and muscle activation are key. In conclusion, while both stretching techniques contribute to improvements, static stretching may offer broader benefits in flexibility.
Thesis (Bachelor of Sports Science)-University of the Philippines Diliman
Includes bibliographies
Keywords: Tae kwon do; Hamstring muscle; Stretching exercises